2012
DOI: 10.1002/agr.21320
|View full text |Cite
|
Sign up to set email alerts
|

Improving Competitiveness of Small‐ and Medium‐Sized Enterprises (SMEs) in Agriproduct Export Business Through ANP: The Turkey Case

Abstract: Agricultural production has considerable potential in Turkey. Different regions of the country are able to supply a variety of agricultural products due to the wide-range of climate conditions and high land quality. Also, the majority of the water resources in the region are located within the country. Hence, with the implementation of the effective agricultural policies, agricultural products can be significantly increased in terms of quality and quantity. In this context, this study investigates findings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Rostek (2012) argues that SME needs to improve competitiveness to survive in a changing environment and strong business competition. Ada et al, (2013) found competitiveness of SME could increase their bargaining position in business competition. Porter (1985) wrote concept of value chain that become basic foundation of competitiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rostek (2012) argues that SME needs to improve competitiveness to survive in a changing environment and strong business competition. Ada et al, (2013) found competitiveness of SME could increase their bargaining position in business competition. Porter (1985) wrote concept of value chain that become basic foundation of competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Research on SME has been developed since the growth of debat upon role of this business organizations to economic development (Gunasekaran et al,2011;Capo-Vicedo et al, 2008). One of the debates that has been emerge among business scholar is how to increased SME competitiveness (Rostek, 2012;Ada et al, 2013). Rostek (2012) argues that SME needs to improve competitiveness to survive in a changing environment and strong business competition.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable innovation can be understood as "innovation that improves sustainability performance, where such performance includes ecological, economic, and social criteria" [7] (p. 2). Several researchers suggest that sustainable innovation is a basic requirement to enhance international business activities [8]. However, much remains to be studied about the mechanisms that facilitate and enhance this relationship [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Rostek (2012), argues that SME needs to improve competitiveness to survive in a changing environment and face increasing business competition. Ada et al, (2013) found competitiveness of SME could increase their bargaining position in business competition. There are variety of levels and approaches actually reflects the wide applications of this concept.…”
Section: Introductionmentioning
confidence: 99%
“…They can be established for all kind of activities of every business and are considered as a back bone of country's economy, specially in the under developed and developing world (Radam al.,2008). Research on SME has been developed since the growth of debut upon role of this business organizations to economic development process (Gunasekaran, A., Rai, B. K., & Griffin, M., 2011 52 the debates that has been emerge among business scholar is how to increased SME competitiveness (Rostek, 2012;Ada et al, 2013). Rostek (2012), argues that SME needs to improve competitiveness to survive in a changing environment and face increasing business competition.…”
Section: Introductionmentioning
confidence: 99%